SIKAP TOLERANSI BERAGAMA DAN KEMAMPUAN BERINTERAKSI SOSIAL SISWA DI KELAS XI SMA NATION STAR ACADEMY SURABAYA - RUDIANTO; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2025)
This study aims to describe students’ religious tolerance attitudes and their social interaction skills, as well as to analyze the relationship between the two among 11th-grade students at Nation Star Academy Senior High School Surabaya. This research employed a quantitative approach with a survey method. Data were collected through questionnaires, observations, and interviews involving 118 respondents selected using total sampling. Data analysis was conducted using Pearson's product-moment correlation with SPSS version 23. The findings show that students’ religious tolerance attitudes fall within the moderate to high category, with most students demonstrating respectful and appreciative behavior toward religious differences in their school environment. Students’ social interaction skills were also found to be strong, as reflected in their ability to communicate across faiths, collaborate in school activities, and resolve conflicts peacefully and inclusively. The analysis reveals a significant and very strong positive correlation between religious tolerance and social interaction skills, with a coefficient of determination (R²) of 0.934. This indicates that 93.4% of the variation in students’ social interaction skills can be explained by their level of religious tolerance. These results suggest that the higher the students’ religious tolerance, the better their social interaction abilities. Overall, this study emphasizes the importance of fostering religious tolerance in educational environments as a fundamental component in shaping inclusive, harmonious, and socially competent students in a multicultural society.